Implementasi Morning Activity dalam Pembinaan Akhlak Mulia Peserta Didik SD Laboratorium Percontohan UPI Kampus Serang - Nurul Safira; Firman Robiansyah; Darmawan Darmawan (ISLAMIKA, 2023)
This study aims to find out, analyze and describe the process of implementing morning activity and the implications of morning activity in fostering students' noble morals. The research approach used is a qualitative approach with a case study method. This study was conducted by taking data in the high class as the main subject through several data collections such as participant obervation, semistructured interviews, and questionnaires. The location of this study is at the UPI Pilot Laboratory Elementary School, Serang Campus. Based on the results of the study, 6 morning activity habituation programs were obtained including dhuha prayers, flag ceremonies, literacy, muraja'ah, tahfidz and tahsin, as well as jumroh / jumsih / skj. The implementation of this activity is carried out before class hours begin according to the schedule of daily activities and in the process of implementation is accompanied by the teacher. The implications of this morning activity on high-grade learners can be seen from the results of a questionnaire filled out by 36 respondents. The results showed that 84% of students answered appropriately and 16% of students answered incorrectly. This shows that there are very large implications of morning activity habituation for the development of noble morals of students, especially for students in grades IV, V, and VI.